STRATEGI PENGAWAS DALAM PEMBINAAN KOMPETENSI PROFESIONALISME GURU (TRANSFORMASI KEPEMIMPINAN DAN MOTIVASI GURU SDN SUNGAI RAYA) - Yanti, Yovi; Anurrahman; Afandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research investigates strategies used by supervisors to enhance teachers' professional competencies related to leadership transformation and motivation at SD Sungai Raya, employing a qualitative approach with 10 participants (1 supervisor, 3 principals, 6 teachers). Data were collected through observation, interviews, and documentation, analyzed in three stages. Key findings include: (1) supervisors effectively enhance competencies by understanding teachers' needs, monitoring regularly, and providing motivation; (2) transformational leadership by principals fosters problem-solving and individual consideration, promoting experience sharing and recognition; (3) teachers exhibit discipline and increased motivation through positive colleague relationships. The study concludes that consistent collaboration among supervisors, principals, and teachers is crucial for improving educational quality.